1998
DOI: 10.1104/pp.116.3.1179
|View full text |Cite
|
Sign up to set email alerts
|

Transit Peptide Mutations That Impair in Vitro and in Vivo Chloroplast Protein Import Do Not Affect Accumulation of the γ-Subunit of Chloroplast ATPase1

Abstract: We have begun to take a genetic approach to study chloroplast protein import in Chlamydomonas reinhardtii by creating deletions in the transit peptide of the ␥-subunit of chloroplast ATPasecoupling factor 1 (CF 1 -␥, encoded by AtpC) and testing their effects in vivo by transforming the altered genes into an atpC mutant, and in vitro by importing mutant precursors into isolated C. reinhardtii chloroplasts. Deletions that removed 20 or 23 amino acid residues from the center of the transit peptide reduced in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…We hypothesized that some cytosolic factors (absents in the in vitro import assays) could play a role in the (⌬1-59)-ceQORH::GFP plastid targeting in planta. In this way, similar differences between in vitro experiments and in planta observations were also described by other authors and indicate that in vitro import assays may not fully match the more complex in vivo situation suggesting that some cytosolic components provide back-up systems to assure import of certain precursors under different environmental conditions (64,65).…”
Section: In Vitro and In Planta Experiments Indicate That The C Termisupporting
confidence: 81%
“…We hypothesized that some cytosolic factors (absents in the in vitro import assays) could play a role in the (⌬1-59)-ceQORH::GFP plastid targeting in planta. In this way, similar differences between in vitro experiments and in planta observations were also described by other authors and indicate that in vitro import assays may not fully match the more complex in vivo situation suggesting that some cytosolic components provide back-up systems to assure import of certain precursors under different environmental conditions (64,65).…”
Section: In Vitro and In Planta Experiments Indicate That The C Termisupporting
confidence: 81%
“…Regardless of the molecular mechanism, however, our findings clearly suggest that accessibility of the N terminus of SS-tp is required for interaction with one or more components of the chloroplast translocation apparatus. Several investigations into the role of different domains of chloroplast transit peptides have also shown that the N terminus is required for precursor import in vitro (24,25), in vivo (26,27), and for directing the import of certain fusion proteins in vitro (8). An intriguing aspect of these reports is that N terminus of some transit peptides is often the least conserved region of the entire presequence (26).…”
Section: Discussionmentioning
confidence: 99%
“…(29, 30, 99) Site-directed mutations in nuclear AtpC gene (114,199) Induced mutations in chloroplast atpE, atpF and atpI genes See (44) Nuclear mutation affecting expression of the chloroplast-encoded atpH and atpI genes…”
Section: Photophosphorylationmentioning
confidence: 99%